School cooperativism in basic education in Mexico:: limitations and opportunities to promote social and solidarity economy - Rosas Baños, Mara; Luvián-Reyes, Gerardo (Cooperativismo & Desarrollo, 2022)
Cooperativism has been used at various educational levels as a socio-pedagogical strategy to not only promote the principles and values of cooperativism, but also to motivate self-management, generate goods and services and a different way of production and interchange. In Mexico, public basic education schools have school cooperatives but their objectives have been significantly restricted from the neoliberal model. The objective of this article is to know the scope of school cooperativism, show the relevance of education in the school regarding the pandemic and explore the opportunities to contribute to training that promotes the Social and Solidarity Economy. The Professor Ocampo Nabor Bolaños Soto Elementary School in Mexico City is used as a case study. It is concluded that school cooperativism is practiced without knowledge or pedagogical support and without a regulation; however, there is still a chance for their rescue.